Conventional Market Brand Equity: How It Affects Visiting Intention - Djatnika, Tjetjep (KnE Social Sciences, 2020)
The aim of this research is to investigate the power of brand equity at a culinary centre in a traditional retail marketplace, assessing whether branding encourages customer visits. Questioners are distributed to visitors. 211 respondents competed the questionnaire survey forms correctly. The collected data were processed statistically using SmartPLS Version 3. The result of analysis reveals that the familiarity of the brand name directly influences brand associations in terms of service, product quality, price policy, and physical environment. Brand associations affect brand trust, and this, in turn, directly affects visit intention. Surprisingly, even though the physical environment of the marketplace has already been modernised by the local government through its revitalisation program, it is not effective in attracting customers. The study suggests that the intention to visit the marketplace stems from the brand name rather than the physical environment of the marketplace. Therefore, the marketplace should focus on developing a strong brand equity, then developing the favourable brand associations and building brand trust to ensure a steady flow of customers. Keywords: brand awareness, brand associations, brand trust, purchase/ visit intention